Evaluating the therapeutic benefits of supporting the psychological health of china’s retired elderly by Chinese freehand painting as a form of art therapy - Abd Shukor, Shureen Faris; Jiamei, Wu; Daud, Mohd Najmi; Hasna, Mohd Fabian (Medwell Publications, 2024)
China's population is aging at an accelerated rate, especially among retirees, which has caused considerable psychological distress. Addressing the mental health of this specific group has become an essential and urgent focus. This study aims to evaluate the efficacy of Chinese freehand painting in promoting the mental health of retired older adults through a comprehensive literature review. This investigation illuminates the process and benefits of integrating art therapy into mental health routines, describing the methodological framework and treatment outcomes associated with this strategy. The study highlights the importance of promoting mental health, the need for interventions the specific methods used. This study also highlights the potential advantages of Chinese freehand painting. Expected outcomes include implementing a comprehensive art therapy approach and evaluating its therapeutic effectiveness. This study provides valuable insights into improving the mental health of retired older adults in China.